Retroreflective aqueous pseudoplastic gel composition for industrial spraying
The aqueous pseudoplastic gel composition addresses the stability and sprayability issues of retroreflective compositions by using specific viscosities and components, enabling stable, high-quality retroreflective layers on diverse substrates through industrial spraying.
Patent Information
- Application Number
- JP2022524583
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-18
- Filing Date
- 2020-11-16
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2040-11-16
AI Technical Summary
Existing retroreflective compositions face challenges in achieving both stability and sprayability, as rheology modifiers for maintaining uniform distribution of spherical glass beads negatively affect rheological behavior during atomization, making them unsuitable for professional or industrial spraying applications.
An aqueous pseudoplastic gel composition is developed, comprising 15-60% water, 20-60% spherical glass beads with a refractive index of 1.8-2.8, 0.15-1.5% thickener, and optional further ingredients, exhibiting viscosities of 5-200 Pa·s at low shear rates and 10-1000 times lower viscosities at high shear rates, allowing for stable and easy application via industrial spraying.
The composition achieves stable, shelf-stable retroreflective layers with excellent homogeneity, wide-angle retroreflectivity, and smoothness, suitable for various substrates, including vertically oriented surfaces, without sagging or inhomogeneity.
Smart Images

Figure 0007620012000008 
Figure 0007620012000009 
Figure 0007620012000010
Abstract
Description
Detailed Description of the Invention
[0001] [Technical field to which the invention pertains] The present invention relates to an aqueous pseudoplastic gel composition and a method for preparing the same. The present invention further relates to a method for coating a substrate with a retroreflective layer using said aqueous pseudoplastic gel composition, and to a substrate coated with a retroreflective layer obtained by said method.
[0002] [Background of the invention] Retroreflective paints, inks and coatings are used in a variety of applications, such as to improve the visibility of road signs, road markers, textiles, automobiles, etc., under low light conditions. Paints, inks and coatings are typically provided with retroreflective properties by the addition of spherical glass beads having a specific refractive index. Retroreflection occurs through the tandem action of refraction of incident light through the upper surface of the spherical glass bead, internal reflection from the lower surface of the spherical glass bead, and subsequent refraction of the light as it exits the upper surface of the spherical glass bead back in the direction from which the incident light came.
[0003] WO2004 / 017104A2 discloses a retroreflective composition comprising retroreflective microspheres, a binder system, and a thixotrope blend comprising at least two thixotropic agents in an amount of about 2 to about 5% by weight based on the retroreflective composition. The composition may include water. The retroreflective composition is intended to be used as a paint, ink, and coating and is applied to a substrate using an aerosol applicator together with a propellant. Table 1 of WO2004 / 017104A2 discloses typical and preferred amounts of classes of components in the composition. Example 1 of WO2004 / 017104A2 discloses a composition in which the solvent is an undefined aliphatic or aromatic naphtha, the solid resin granules are an undefined acrylic type, the first thixotrope is an undefined polyurea type, and the second thixotrope is an undefined calcium sulfonate complex. The associated viscosity of the composition of Example 1 measured at 25° C. using a Brookfield #3 spindle will be 9,000-30,000 cps at 0.5 rpm and 600-1,900 cps at 20 rpm.
[0004] WO01 / 16223A1 relates to retroreflective inks for printing on textiles. A single embodiment of WO01 / 16223A1 discloses a screen printing ink. This screen printing ink is · 3 parts 409 AG Reflective Clear LF base (containing water and spherical glass beads and matrix material); 1 part Grancill PWX binding and finishing agent (which contains water as a volatile component); and 2% by volume of CX100 crosslinker, based on the combined volume of 409 AG Reflective Clear LF base and Grancill PWX It consists of:
[0005] The viscosity of 409 AG Reflective Clear LF Base is stated to be approximately 0.090-0.110 centistokes. The kinematic viscosity v [cSt] is related to the dynamic viscosity μ [Pa s] as follows:
[0006]
number
[0007] 1300g / m 3Considering a realistic estimation of the density ρ of 409 AG Reflective Clear LF Base, the dynamic viscosity μ of 409 AG Reflective Clear LF Base is 0.12-0.14 MPa·s. As will be appreciated by those skilled in the art, a viscosity more than 7 times lower than water is simply not possible with a mixture of water, (significant amounts of) glass beads, binders, finishes, and further volatile components. The viscosity of the final screen printing ink is not disclosed in the examples of WO01 / 16223A1. Screen printing is a printing technique in which a mesh is used to transfer a paste-like ink onto a substrate, except in areas made impermeable to the ink by a blocking stencil. A blade or squeegee is moved across the screen to fill the open mesh openings with ink, and then a reverse stroke brings the screen into momentary contact with the substrate along the contact line. This causes the ink to wet the substrate and be drawn out of the mesh openings as the screen bounces back after the blade has passed. As is generally known to those skilled in the art of printing, the rheological properties of inks for screen printing and inks for professional or industrial (high speed) spraying are fundamentally different due to the distinct techniques used to apply them to the substrate: screen printing inks are not suitable for professional or industrial (high speed) spraying.
[0008] WO00 / 42113A1 relates to a retroreflective ink comprising microbeads in a liquid carrier medium. The liquid carrier medium can be water. The ink is intended for screen printing onto textiles. WO00 / 42113A1 discloses that the viscosity of the screen printing ink is 10-30 Pa·s at room temperature, measured with a Brookfield viscometer using a #5 spindle rotating at 10 rpm. The inks disclosed in Tables 1-4 and 6 comprise water, a thickener, and glass beads. The viscosity is 12.3-32 Pa·s at room temperature, measured with a Brookfield viscometer using a #5 spindle rotating at 10 rpm. As explained above, in the context of WO01 / 16223A1, it is generally known to those skilled in the art of printing that the rheological properties of inks for screen printing and inks for professional or industrial (high speed) spraying are fundamentally different, since the techniques used to apply them to the substrate are fundamentally different.
[0009] Developing retroreflective compositions that have both good stability and sprayability is a challenge because rheology modifiers are required to maintain retroreflective particles such as spherical glass beads - which typically have a density substantially higher than that of the fluid carrier - which, when distributed uniformly throughout the fluid carrier, generally have a negative impact on the rheological behavior during spraying.
[0010] There is a need for retroreflective inks, coatings and paints that are shelf stable, preferably yet can be easily applied to a variety of substrates using professional or industrial (high velocity) spraying, and result in retroreflective layers or coatings that have good quality.
[0011] It is therefore an object of the present invention to provide an aqueous retroreflective composition that can be professionally or industrially applied to a variety of substrates as a paint, ink or coating, wherein the aqueous retroreflective composition can be applied to the substrate by spraying, such as professional or industrial (high velocity) spraying, and wherein the aqueous retroreflective composition has sufficient stability or shelf life.
[0012] It is a further object of the invention to provide an aqueous retroreflective composition that can be professionally or industrially applied to a variety of substrates by spraying, such as professional or industrial (high speed) spraying, as a paint, ink or coating, and that results in good or improved print or coating qualities, such as good or improved uniformity of the layer and retroreflectivity at wide angles, preferably good or improved smoothness and cleanliness of the layer.
[0013] [Summary of the Invention] The inventors have -1 The first viscosity η1 is 5 to 200 Pa s at a shear rate of 100 s -1 It has been unexpectedly established that one or more of the objectives can be met by using an aqueous retroreflective composition that is an aqueous pseudoplastic gel composition having a second viscosity η2 that is 10 to 1000 times lower than the first viscosity at a shear rate of .
[0014] Thus, in a first aspect, the present invention provides an aqueous pseudoplastic gel composition, preferably for professional or industrial (high velocity) spraying, having a viscosity of 0.01 s -1 The first viscosity η1 is 5 to 200 Pa s at a shear rate of 100 s -1 and a second viscosity η2 that is 10 to 1000 times lower than the first viscosity at a shear rate of ... 15-60% by weight water; 20-60% by weight of spherical glass beads having a median particle size D50 measured by laser diffraction of 5-150 μm, preferably 20-150 μm, and a refractive index measured at a wavelength λ of 589 nm of 1.8-2.8, optionally at least a portion of said spherical glass beads being hemispherically coated with a light-reflective coating; 0.15-1.5% by weight of a thickening agent; and 0-50% by weight of one or more further ingredients; and the viscosity is measured at a temperature of 25° C. with a rheometer having plate-plate geometry and a gap distance of 0.5 mm.
[0015] The inventors have established that the aqueous pseudoplastic gel composition can be applied to various substrates, for example using industrial high-speed spraying, resulting in a retroreflective coating layer with excellent print or coating qualities, such as uniformity and retroreflectivity at wide angles. When the retroreflective coating comprises one or more additional transparent coating layers, a retroreflective layer with high smoothness and good washability can be obtained. Unexpectedly, these results can also be obtained when the aqueous pseudoplastic gel composition is applied to the surface of a vertically arranged substrate.
[0016] In a second aspect, there is provided a method for the preparation of an aqueous pseudoplastic gel composition as defined herein, the method comprising: (i) adding water, spherical glass beads as defined herein, a thickening agent as defined herein and optionally one or more further ingredients as defined herein to a container; (ii) stirring or homogenizing the mixture obtained in step (i) preferably at a temperature of 15-30° C., preferably for a period of 5-15 minutes; and (iii) optionally, before or after step (ii), adjusting the pH, preferably to a value between 6.0 and 11, more preferably to a value between 7.0 and 11. Includes.
[0017] In a third aspect, there is provided a method for the preparation of an aqueous pseudoplastic gel composition as defined herein, the method comprising: (i) adding water, spherical glass beads as defined herein, at least a portion of the thickening agent as defined herein, and optionally a portion of one or more further ingredients as defined herein to a container; (ii) stirring or homogenizing the mixture obtained in step (i) preferably at a temperature of 15-30° C., preferably for a period of 5-15 minutes; (iii) optionally adjusting the pH before or after step (ii), preferably to a value between 6.0 and 11, more preferably to a value between 7.0 and 11; (iv) adding to the composition obtained in step (ii) or (iii) at least a portion of one or more further ingredients as defined herein, optionally adding a portion of a thickening agent as defined herein, and optionally adding water; (v) stirring or homogenizing the mixture obtained in step (iv) at a temperature preferably between 15 and 30° C., preferably for a period of time between 5 and 15 minutes; and (vi) optionally, before or after step (v), adjusting the pH, preferably to a value between 6.0 and 11, more preferably to a value between 7.0 and 11; Includes.
[0018] In a fourth aspect of the present invention, there is provided a method for the preparation of an aqueous pseudoplastic gel composition as defined herein, the method comprising: (i) adding water, spherical glass beads as defined herein, at least a portion of the thickening agent as defined herein, and optionally a portion of one or more further ingredients as defined herein to a container; (ii) stirring or homogenizing the mixture obtained in step (i) at a temperature preferably between 5 and 30° C., preferably for a period of time between 5 and 15 minutes, to obtain an intermediate aqueous pseudoplastic gel composition having the composition and properties of the aqueous pseudoplastic gel composition defined herein; (iii) optionally adjusting the pH before or after step (ii), preferably to a value between 6.0 and 11, more preferably to a value between 7.0 and 11; (iv) adding at least a portion of one or more further ingredients as defined herein, optionally a portion of a thickening agent as defined herein, and optionally water to the intermediate aqueous pseudoplastic gel composition obtained in step (ii) or (iii); (v) stirring or homogenizing the mixture obtained in step (iv) at a temperature of preferably 15 to 30° C. for preferably 5 to 15 minutes to obtain an aqueous pseudoplastic gel composition; and (vi) optionally, before or after step (v), adjusting the pH, preferably to a value between 6.0 and 11, more preferably to a value between 7.0 and 11; Includes.
[0019] In a fifth aspect, the present invention relates to a method of coating a substrate with a retroreflective layer, the method comprising: (a) providing a substrate; (b) optionally applying a primer layer to the substrate of step (a); (c) spraying an aqueous pseudoplastic gel composition as defined herein onto the substrate of step (a) or onto the primed substrate of step (b) to provide a substrate coated with a retroreflective layer; (d) optionally drying the substrate coated with the retroreflective layer obtained in step (c); and (e) coating the retroreflective layer-coated substrate obtained in step (c) or the dried retroreflective layer-coated substrate obtained in step (d) with one or more additional transparent coating layers, followed by drying or curing. Includes.
[0020] In a sixth aspect, the present invention relates to a substrate coated with a retroreflective layer obtainable by the method for coating a substrate defined herein.
[0021] [Definition] The term "pseudoplastic gel" as used herein refers to a gel that exhibits shear thinning behavior and does not have a yield point.
[0022] The term "shear thinning behavior" in the context of the pseudoplastic gels of the present invention relates to the decrease in viscosity when the pseudoplastic gel is initially in a static state and is subjected to a shear rate.
[0023] The term "tan(δ)" (where δ is the phase shift) is defined by the ratio G" / G', as commonly known in the art of rheology. G" represents the loss modulus and characterizes the viscous or liquid-like behavior of the sample. G' represents the storage modulus and characterizes the elastic or solid-like behavior of the sample. If the sample exhibits purely viscous and no elastic behavior, then δ=90°, G'=0 and tan(δ)=∞. If the sample exhibits purely elastic and no viscous behavior, then δ=0°, G"=0 and tan(δ)=0. If the sample has a non-zero phase shift δ of less than 45°, then tan(δ) is less than 1, G' is greater than G", and the sample exhibits gel-like behavior in the sense that the elastic behavior dominates the viscous behavior. [Brief description of the drawings]
[0024] [Figure 1] 1 shows the viscosity versus shear rate profile of an aqueous pseudoplastic gel composition according to the present invention. [Diagram 2] 2 shows the thixotropic behavior of the aqueous pseudoplastic gel composition of FIG. 1. [Diagram 3] 1 shows the tan(δ) profile as a function of vibration frequency for an aqueous pseudoplastic gel composition according to the present invention.
[0025] [Detailed Description] In a first aspect, the present invention provides an aqueous pseudoplastic gel composition, preferably for professional or industrial (high velocity) spraying, having a viscosity of 0.01 s -1 The first viscosity η1 is 5 to 200 Pa s at a shear rate of 100 s -1 and a second viscosity η2 that is 10 to 1000 times lower than the first viscosity at a shear rate of ... 15-60% by weight water; 20-60% by weight of spherical glass beads having a median particle size D50 measured by laser diffraction of 5-150 μm, preferably 20-150 μm, and a refractive index measured at a wavelength λ of 589 nm of 1.8-2.8, optionally at least a portion of said spherical glass beads being hemispherically coated with a light-reflective coating; 0.15-1.5% by weight of a thickening agent; and 0-50% by weight of one or more further ingredients and the viscosity is measured at a temperature of 25° C. with a rheometer having plate-plate geometry and a gap distance of 0.5 mm.
[0026] In preferred embodiments, the aqueous pseudoplastic gel composition is stable for at least 1 day, more preferably at least 2 days, at least 5 days, at least 10 days, at least 1 month, at least 2 months, at least 6 months, at least 1 year, at least 2 years, where a composition is considered stable when no settling, syneresis and separation can be observed upon visual and tactile inspection.
[0027] The aqueous pseudoplastic gel composition as defined herein is preferably an ink, paint or coating formulation.
[0028] Spherical Glass Beads As defined above, the refractive index of the spherical glass beads is between 1.8 and 2.8, measured at a wavelength λ of 589 nm.
[0029] The term "glass" in "spherical glass beads" as used herein refers to a non-crystalline, amorphous solid and transparent material made from oxides. The refractive index of spherical glass beads is closely related to the density of glass, but the relationship is not linear. Due to the nature of glass, the density is approximately an additive function of its composition. The density of spherical glass beads with a refractive index of 1.5 to 2.8 is typically 2.5 to 4.5 g / cm 3 The time varies between 0 and 100 ms.
[0030] Oxides which can be used in the glass are the oxides of silicon, boron, aluminum, sodium, barium, vanadium, titanium, lanthanum, strontium, zirconium, potassium, magnesium, iron, calcium, zinc, lithium, barium and lead. Spherical glass beads can include, for example, various combinations of silica (SiO2), boron oxide (B2O3), phosphorus pentoxide (P2O5), vanadium pentoxide (V2O5), arsenic trioxide (As2O3), germanium oxide (GeO2), calcium oxide (CaO), sodium oxide (Na2O), magnesium oxide (MgO), zinc oxide (ZnO), aluminum oxide (Al2O3), potassium oxide (K2O), iron oxide (Fe2O3), lead oxide (PbO), barium oxide (BaO), barium titanate (BaTiO3), titanium oxide (TiO2), lithium oxide (Li2O), strontium oxide (SrO), lanthanum oxide (La2O3), and zirconium oxide (ZrO2). Silica and boron oxide generally have the lowest density. Thus, glasses containing large weight percentages of these oxides generally result in glass beads with low refractive index. The refractive index can be increased by adding oxides with higher molecular weights.
[0031] Preferably, the spherical glass beads are PbO-free.
[0032] Glass beads having a refractive index in the range of 1.5 to 2.51 and their oxide compositions are disclosed in WO2014 / 109564A1, which is incorporated herein by reference in its entirety. PbO-free transparent glass beads having a refractive index greater than 2.15 are disclosed in U.S. Patent No. 4,082,427, which is incorporated herein by reference in its entirety.
[0033] The spherical glass beads may be colored spherical glass beads as long as they are transparent. Both colored spherical glass beads made from colored transparent glass and spherical glass beads with a concentric transparent color coating are included in the present invention. The color may be a natural color caused by the composition of oxides, or may be intentionally selected by adding a component with a specific color. Colored glass beads with high refractive index and high transparency are disclosed in WO2014 / 109564A1.
[0034] Thus, in one embodiment, at least some of the spherical glass beads are made from a colored transparent glass and / or at least some of the spherical glass beads include a concentric transparent colored coating.
[0035] The spherical glass beads have a median diameter D50 as measured by laser diffraction. The median diameter D50 is therefore the volume median based on the volume distribution. The median diameter D50 is the diameter below which half of the population of spherical glass beads lies. This volume median diameter is also known in the art as Dv50 or Dv 0.5 It is often referred to as.
[0036] In a preferred embodiment, the spherical glass beads have a median particle size D50, as measured by laser diffraction, of 25-100 μm, preferably 30-75 μm, more preferably 35-50 μm.
[0037] In another preferred embodiment, the spherical glass beads have a median particle size D50 of 5 to 100 μm, such as 5 to 75 μm, 5 to 50 μm, 5 to 45 μm, 5 to 40 μm or 5 to 35 μm, as measured by laser diffraction.
[0038] In yet another preferred embodiment, the spherical glass beads have a median particle size D50 of 25-150 μm, such as 50-150 μm, 75-150 μm, 100-150 μm, 110-150 μm or 115-150 μm, as measured by laser diffraction.
[0039] The diameters D10 and D90 are referred to in the art as Dv10 or Dv 0.1 and Dv90 or Dv 0.9 The D10 diameter is the diameter below which 10% of the spherical glass beads fall. Similarly, the D90 diameter is the diameter below which 90% of the spherical glass beads fall.
[0040] The span of the particle size distribution of spherical glass beads, as measured by laser diffraction, is defined by the following formula:
[0041]
number
[0042] In a further preferred embodiment, the spherical glass beads have a median particle size D50 of 25-100 μm and a span of 0-1, preferably 0-0.7, more preferably 0-0.5, even more preferably 0-0.2, even more preferably 0-0.1, as measured by laser diffraction. In a further preferred embodiment, the spherical glass beads have a median particle size D50 of 30-75 μm and a span of 0-1, preferably 0-0.7, more preferably 0-0.5, even more preferably 0-0.2, even more preferably 0-0.1, as measured by laser diffraction. In an even further preferred embodiment, the spherical glass beads have a median particle size D50 of 35-50 μm and a span of 0-1, preferably 0-0.7, more preferably 0-0.5, even more preferably 0-0.2, even more preferably 0-0.1, as measured by laser diffraction.
[0043] In another more preferred embodiment, the spherical glass beads have a median particle size D50 of 5-35 μm and a span of 0-2, such as 0-1.8, 0-1.5, 0-1.25 and 0-1, or such as 0.5-2, 1-2 and 1.25-2, as measured by laser diffraction.
[0044] In another even more preferred embodiment, the spherical glass beads have a median particle size D50 of 10-25 μm and a span of 0-2, such as 0-1.8, 0-1.5, 0-1.25 and 0-1, or such as 0.5-2, 1-2 and 1.25-2, as measured by laser diffraction.
[0045] As will be appreciated by those skilled in the art, span=0 corresponds to monodisperse spherical glass beads.
[0046] In a preferred embodiment, at least a portion of the spherical glass beads are hemispherically coated with a light-reflective coating. One example is a hemispherical aluminum coating. This is possible, but not necessary to provide the benefits described herein. Thus, in one embodiment, the spherical glass beads are not hemispherically coated with a light-reflective coating.
[0047] In a preferred embodiment, the amount of spherical glass beads is 25-55% by weight, more preferably 26-52% by weight, and even more preferably 27-50% by weight, based on the total weight of the aqueous pseudoplastic gel composition.
[0048] In embodiments, the amount of spherical glass beads is 20-55 wt%, 20-50 wt%, 20-45 wt%, 20-40 wt%, 20-35 wt%, 20-30 wt%, or 20-25 wt%, based on the total weight of the aqueous pseudoplastic gel composition.
[0049] In other embodiments, the amount of spherical glass beads is 22-60 wt%, 25-60 wt%, 30-60 wt%, 35-60 wt%, 40-60 wt%, 45-60 wt%, 50-60 wt%, or 55-60 wt%, based on the total weight of the aqueous pseudoplastic gel composition.
[0050] The particular application of the aqueous pseudoplastic gel composition will determine the optimum refractive index of the spherical glass beads. When the composition is applied in a dry environment or on a substrate that exhibits retroreflectivity under dry conditions, and the applied layer of retroreflective spherical glass beads is not coated with an additional layer, the refractive index of the spherical glass beads, measured at a wavelength λ of 589 nm, may be between 1.8 and 2.8.
[0051] In one embodiment, the aqueous pseudoplastic gel composition defined herein comprises spherical glass beads having a refractive index of 1.8 to 2.0 measured at a wavelength λ of 589 nm.
[0052] On the other hand, when the composition is applied in a wet environment or on a substrate that exhibits retroreflectivity under wet conditions, or when the applied layer of retroreflective spherical glass beads is coated with one or more further transparent layers, the refractive index of the spherical glass beads measured at a wavelength λ of 589 nm is preferably 2.0 to 2.8, more preferably 2.2 to 2.4. Compositions that exhibit retroreflectivity under both dry and wet conditions, where the applied layer of retroreflective spherical glass beads is coated or uncoated with one or more further transparent layers, can comprise different types of glass beads having different refractive indices and optionally different sizes. In one embodiment, the aqueous pseudoplastic gel composition defined herein comprises spherical glass beads having a refractive index measured at a wavelength λ of 589 nm of 2.0 to 2.8, preferably 2.2 to 2.4.
[0053] In another embodiment, the aqueous pseudoplastic gel composition defined herein comprises at least two types of spherical glass beads, at least one type of spherical glass bead having a refractive index, measured at a wavelength λ of 589 nm, between 1.8 and less than 2.0, and at least one further type of spherical glass bead having a refractive index, measured at a wavelength λ of 589 nm, between 2.0 and 2.8.
[0054] Thickener The aqueous pseudoplastic gel composition includes a thickening agent. Without wishing to be bound by any theory, it is believed that the thickening agent limits or prevents the precipitation and / or settling of the spherical glass beads and optionally further particulate matter in the aqueous pseudoplastic gel composition. Furthermore, without wishing to be bound by any theory, it is believed that the thickening agent imparts shear thinning behavior to the gel composition.
[0055] In embodiments, the thickening agent comprises a mixture of different thickening agents. In a preferred embodiment, the thickening agent consists of a single thickening agent.
[0056] One preferred group of thickeners are ASE polymers (alkali swellable emulsions). These polymers are produced using emulsion polymerization. ASE polymers are based on a balance of hydrophilic (meth)acrylic acid monomers and hydrophobic (meth)acrylate ester monomers and can be delivered in liquid form at high volume solids. ASE polymers rely on a change from low to high pH (neutralization) to trigger thickening. The "trigger" is incorporated into the polymer by creating an approximately 50:50 ratio of water-soluble (meth)acrylic acid and water-insoluble (meth)acrylate ester. If the acid is not neutralized (low pH), the polymer is insoluble in water and will not thicken. If the acid is fully neutralized (high pH), the polymer becomes soluble and thickens. ASE polymers are delivered at low pH (<5) and maintain low delivered viscosity (<100 cP) at solids up to 35%. When exposed to a pH of about 7 or higher, ASE polymers solubilize, swell, and thicken compositions by volume exclusion. The degree of thickening can be related to the molecular weight of the polymer. Because their performance depends on water absorption and swelling, ASE polymers tend to have very high molecular weights, which allows them to thicken efficiently. The rheological profile that ASE polymers create is typically steeply shear thinning (pseudoplastic), and therefore ASE polymers are well suited to building high viscosities at very low shear rates.
[0057] In one embodiment, the hydrophilic monomer of the ASE polymer is selected from the group consisting of (meth)acrylic acid, maleic acid, and combinations thereof.
[0058] In another embodiment, the hydrophobic monomers of the ASE polymer are selected from the group consisting of esters of (meth)acrylic acid with C1-C4-alcohols, in particular ethyl acrylate, butyl acrylate and methyl methacrylate.
[0059] In yet another preferred embodiment, the hydrophilic monomer of the ASE polymer is selected from the group consisting of (meth)acrylic acid, maleic acid and combinations thereof, and the hydrophobic monomer of the ASE polymer is selected from the group consisting of esters of (meth)acrylic acid with C1-C4-alcohols, in particular ethyl acrylate, butyl acrylate and methyl methacrylate.
[0060] In one embodiment, the ASE polymer comprises 10-90% by weight of repeat units based on one or more hydrophilic monomers A and 10-90% by weight of repeat units based on one or more hydrophobic monomers B, the amounts of monomers A and B adding up to 100% by weight, based on the weight of the ASE polymer.
[0061] [ka] In the formula, R1 and R2 are independently hydrogen or methyl, and R3 is C1-C4-alkyl.
[0062] Another preferred group of thickeners are HASE polymers (hydrophobically modified alkali swellable emulsions, these polymers are produced using emulsion polymerization). HASE polymers are copolymers built on ASE polymer chemistry by adding one or more hydrophobic associative monomers (e.g., acrylic ester and / or vinyl ester monomers) to the ASE polymer composition. HASE polymers retain the pH-dependent behavior of their ASE counterparts, but in addition to absorbing water, HASE polymers also thicken through hydrophobic associations. This mechanism is known as associative thickening (i.e., associative thickeners). (Associate with any hydrophobic moieties in the composition).
[0063] The hydrophilic and hydrophobic monomers of the HASE polymers can be the same as those described for the ASE polymers. Preferred hydrophobic associative monomers are (meth)acrylic acid and C8-C 22 -(meth)acrylic acid ester monomers of alcohols and / or (substituted) vinyl alcohols and C8-C 22 In another preferred embodiment, the one or more hydrophobic associative monomers are selected from the group consisting of steareth-20 methacrylate, beheneth-25 methacrylate, vinyl neodecanoate, and combinations thereof.
[0064] In one embodiment, the HASE polymer comprises, based on the weight of the HASE polymer, 10-90% by weight of repeat units based on one or more hydrophilic monomers A as defined above, 10-90% by weight of repeat units based on one or more hydrophobic monomers B as defined above, and 0.01-2% by weight of repeat units based on one or more hydrophobic associative monomers C and / or D, the amounts of monomers A, B, C and D totaling 100% by weight.
[0065] [ka] In the formula, R4 is hydrogen or methyl, and R5 is a C8-C22 -alkyl, n is an integer from 0 to 50, R6 is hydrogen or methyl, and R7 is C 22 -alkyl.
[0066] Yet another preferred group of thickeners are hydrophobically modified ethoxylated urethane (HEUR) polymers. Unlike ASE or HASE type thickeners, HEUR polymers are non-ionic and soluble at any pH. This solubility is due to the ethylene oxide backbone of the polymer, which is water-soluble and constitutes the majority of the polymer structure. Therefore, HEUR polymers require hydrophobic moieties in the composition to interact with the ethylene oxide backbone to provide structure.
[0067] Examples of ASE polymers include Rheovis® 1125 (available from BASF Corporation), ACULYN™ 33, ACULYN™ 38, ACUSOL™ 810A, ACUSOL™ 830, ACUSOL™ 835, ACUSOL™ 842 (all available from DOW Chemical), and Carbopol® Aqua 30 polymer (from Lubrizol Corporation).
[0068] Examples of HASE polymers include ACULYN™ Excel, ACRYSOL™ TT615, ACULYN™ 22, ACULYN™ 88, ACUSOL™ 801S, ACUSOL™ 805S, ACUSOL™ 820 and ACUSOL™ 823 (all available from DOW Chemical).
[0069] Examples of HEUR polymers include ACUSOL™ 880, ACUSOL™ 882, ACULYN™ 44 and ACULYN™ 46N (all available from DOW Chemical).
[0070] In yet another embodiment, the thickening agent is selected from the group consisting of acrylate crosspolymers, crosslinked polyacrylic acid polymers and crosslinked polyacrylic acid copolymers, particularly Carbopol® polymer products from Lubrizol Corporation, such as Carbopol® AQUA SF-1 polymer, Carbopol® AQUA SF-1 OS polymer and Carbopol® Aqua SF-3 polymer.
[0071] In yet another embodiment, the thickening agent is selected from the group consisting of liquid acrylic crosslinked or copolymer dispersions.
[0072] In yet another embodiment, the thickener is selected from non-ionic aqueous emulsions of modified ethylene vinyl acetate copolymer waxes, such as Aquatix 8421 available from BYK.
[0073] In yet another embodiment, the thickener is selected from modified ureas or urea modified polyamides, such as Rheobyk-420 available from BYK.
[0074] In one embodiment, the thickening agent is selected from the group consisting of ASE polymers, HASE polymers, HEUR polymers, liquid acrylic crosslinked or copolymer dispersions, acrylate crosspolymers, crosslinked polyacrylic acid polymers, crosslinked polyacrylic acid copolymers, non-ionic aqueous emulsions of modified ethylene vinyl acetate copolymer waxes, modified ureas or urea modified polyamides, and combinations thereof.
[0075] In another embodiment, the thickening agent is selected from the group consisting of ASE polymers, HASE polymers, HEUR polymers, liquid acrylic crosslinked or copolymer dispersions, acrylate crosspolymers, crosslinked polyacrylic acid polymers, crosslinked polyacrylic acid copolymers, non-ionic aqueous emulsions of modified ethylene vinyl acetate copolymer waxes, and combinations thereof.
[0076] In another embodiment, the thickening agent is selected from the group consisting of ASE polymers, HASE polymers, HEUR polymers, liquid acrylic crosslinked or copolymer dispersions, crosslinked polyacrylic acid polymers, crosslinked polyacrylic acid copolymers, and combinations thereof.
[0077] In yet another embodiment, the thickening agent is selected from the group consisting of ASE polymers, HASE polymers, and combinations thereof. In one embodiment, the thickening agent is selected from the group consisting of ASE polymers and combinations thereof. In another embodiment, the thickening agent is selected from the group consisting of HASE polymers and combinations thereof.
[0078] In a preferred embodiment, the amount of the thickener is 0.20 to 1.4 wt %, more preferably 0.25 to 1.3 wt %, and even more preferably 0.30 to 1.2 wt %, based on the total weight of the aqueous pseudoplastic gel composition.
[0079] In some embodiments, the amount of thickener is 0.15-1.4 wt%, 0.15-1.3 wt%, 0.15-1.2 wt%, 0.15-1.1 wt%, 0.15-1.0 wt%, 0.15-0.9 wt%, 0.15-0.8 wt%, 0.15-0.7 wt%, 0.15-0.6 wt%, 0.15-0.55 wt%, 0.15-0.5 wt%, or 0.15-0.45 wt%, based on the total weight of the aqueous pseudoplastic gel composition.
[0080] In other embodiments, the amount of thickener is 0.20-1.5 wt%, 0.25-1.5 wt%, 0.30-1.5 wt%, 0.35-1.5 wt%, 0.40-1.5 wt%, 0.45-1.5 wt%, 0.50-1.5 wt%, 0.55-1.5 wt%, or 0.6-1.5 wt%, based on the total weight of the aqueous pseudoplastic gel composition.
[0081] The amount of water in the aqueous pseudoplastic gel composition is specified independently. If the thickener is applied, for example, in the form of a dispersion in water, the amount of thickener defined above relates to the dry weight of the thickener.
[0082] Further ingredients In preferred embodiments, the one or more additional components are selected from the group consisting of wetting agents, preservatives, dyes, luminescent agents (e.g., phosphorescent and fluorescent agents), pigments, UV absorbers, binders and resins, mica flake pigments, and metal flakes or powders.
[0083] Non-limiting examples of wetting agents that can be used are 2,3-propanediol, ethylene glycol, and butylene glycol.
[0084] Examples of binders and resins that can be used are water-based binders and resins, such as aqueous dispersions of binders and resins.
[0085] Metal flakes or powders can be used as reflective pigments. Examples are aluminum, bronze, copper, gold, silver, tin and nickel flakes, preferably aluminum flakes. The size of the flakes is typically substantially smaller than the size of spherical glass beads.
[0086] Mica flake pigments can also be used as reflective pigments, such as pearlescent pigments based on mica flakes.
[0087] In embodiments, the amount of one or more additional components is 0-45 wt%, 0-40 wt%, 0-35 wt%, 0-30 wt%, 0-25 wt%, 0-20 wt%, 0-15 wt%, 0-10 wt%, or 0-5 wt%, based on the total weight of the aqueous pseudoplastic gel composition.
[0088] In other embodiments, the amount of one or more additional components is 5-50%, 10-50%, 15-50%, 20-50%, 25-50%, 30-50%, 35-50%, 40-50% or 45-50% by weight based on the total weight of the aqueous pseudoplastic gel composition.
[0089] The amount of water in the aqueous pseudoplastic gel composition is specified independently. If one or more additional components are applied, for example, in the form of a dispersion in water, the amount of the one or more additional components defined above relates to the dry weight, i.e. the weight without water, of the one or more additional components.
[0090] Rheological behavior The aqueous gel composition has pseudoplastic behavior, which means that it has shear thinning behavior without exhibiting a yield point. This means that the composition is gel-like but still capable of flowing in a static / stable situation (no shear) and also gel-like (and capable of flowing) at increased shear rates. In other words, the aqueous gel composition is gel-like but is nevertheless pourable. Furthermore, if the static / stable state is disturbed by subjecting the gel to a certain increased shear rate (shear thinning behavior), the viscosity decreases.
[0091] The aqueous pseudoplastic gel composition according to the invention is preferably characterized in that the tan(δ) value, measured with a rheometer having plate-plate geometry and a gap distance of 0.5 mm at a temperature of 25° C. and an oscillation frequency of 10 to 0.1 Hz, is less than 1. In a preferred embodiment, the tan(δ) value, measured with a rheometer having plate-plate geometry and a gap distance of 0.5 mm at a temperature of 25° C. and an oscillation frequency of 10 to 0.1 Hz, is 0.1 to 0.9, more preferably 0.2 to 0.8.
[0092] As will be appreciated by those skilled in the art, the tan(δ) value is measured at a suitable shear strain within the linear viscoelastic range.
[0093] As defined above, the aqueous pseudoplastic gel composition has a viscosity of 0.01 s -1 The first viscosity η1 is 5 to 200 Pa s at a shear rate of 100 s -1The composition has a second viscosity η2 that is 10 to 1000 times lower than the first viscosity at a shear rate of 100 / s. In a preferred embodiment, the first viscosity is 10 to 190 Pa·s, more preferably 14 to 180 Pa·s, even more preferably 16 to 150 Pa·s, even more preferably 18 to 120 Pa·s, and even more preferably 20 to 80 Pa·s. In another preferred embodiment, the second viscosity is 0.05 to 2 Pa·s, more preferably 0.08 to 1 Pa·s, even more preferably 0.1 to 0.8 Pa·s, even more preferably 0.12 to 0.7 Pa·s, even more preferably 0.15 to 0.6 Pa·s, and most preferably 0.2 to 0.5 Pa·s.
[0094] In yet another embodiment, the aqueous pseudoplastic gel composition comprises a 0.01s -1 The first viscosity η1 is 5 to 50 Pa s at a shear rate of 100 s -1 has a second viscosity η2 that is 10 to 200 times lower than the first viscosity at a shear rate of
[0095] In yet another embodiment, the aqueous pseudoplastic gel composition comprises a 0.01s -1 The first viscosity η1 is 5 to 50 Pa s at a shear rate of 100 s -1 The viscosity of the polymer solution is 0.15 to 0.6 Pa·s, and preferably 0.2 to 0.5 Pa·s, at a shear rate of 100° C.
[0096] In yet another embodiment, the aqueous pseudoplastic gel composition is -1 First viscosity η1 of 100-200 Pa s at a shear rate of 100 s -1 and has a second viscosity η2 that is 200 to 1000 times lower than the first viscosity.
[0097] In another embodiment, the aqueous pseudoplastic gel composition comprises a 0.01s -1 The first viscosity η1 is 100-200 Pa s at a shear rate of 100 s -1 The viscosity of the polymer solution is 0.15 to 0.6 Pa·s, and preferably 0.2 to 0.5 Pa·s, at a shear rate of 100° C.
[0098] 0.01s-1 The gel structure and first viscosity of the aqueous pseudoplastic gel composition, measured at a shear rate of 100 s, is sufficient to maintain the spherical glass beads and any additional particulate materials in suspension for an extended period of time. -1 The shear rate of 100 s is typical of (industrial) spraying conditions under which the aqueous pseudoplastic gel composition can be applied to a substrate. The second viscosity is 100 s -1 and is sufficiently low to provide an aqueous pseudoplastic gel composition that can be easily sprayed.
[0099] The present inventors have found that the aqueous pseudoplastic gel composition of the present invention has a viscosity of 100 s -1 It has been established that after applying a shear rate of 100 Hz, the first viscosity is recovered in a relatively short time (thixotropy test). This phenomenon is very advantageous for obtaining a smooth and homogeneous layer that does not show sagging behavior.
[0100] Thus, in a preferred embodiment, the aqueous pseudoplastic gel composition as defined herein has a shear rate of 0.1 s -1 and the aqueous pseudoplastic gel composition has a third viscosity η3, and the aqueous pseudoplastic gel composition is subjected to the successive steps: (i) The aqueous pseudoplastic gel composition is mixed with water for 0.1 s. -1 for at least 30 seconds and measuring the third viscosity η3; (ii) The aqueous pseudoplastic gel composition is subjected to 100 s -1 for 30 seconds; (iii) Shear rate is reduced to 0.1 s -1 and (iv) measuring the viscosity of the aqueous pseudoplastic gel composition as a function of time and comparing it to the value of the third viscosity η3. recovers at least 20%, preferably at least 30%, more preferably at least 50%, even more preferably at least 70% of the value of the third viscosity η3 within 10 seconds, preferably within 5 seconds, more preferably within 2 seconds of the reduction in shear rate in step (iii) of the method comprising: wherein the viscosity is measured in a rheometer having a plate-plate geometry and a gap distance of 0.5 mm at a temperature of 25°C.
[0101] The expression "recovering at least x% of the value of the third viscosity η3 within a certain time" as used in the context of the present invention means that the viscosity actually reaches a value of xη3 / 100 within that time.
[0102] This embodiment can also be expressed as follows: In a preferred embodiment, the aqueous pseudoplastic gel composition as defined herein has a viscosity of 0.1 s -1 and the aqueous pseudoplastic gel composition has a third viscosity η3 at a shear rate of 1000 nm to 1500 nm. (i) The aqueous pseudoplastic gel composition is mixed with water for 0.1 s. -1 for at least 30 seconds and measuring the third viscosity η3; (ii) The aqueous pseudoplastic gel composition is subjected to 100 s -1 for 30 seconds; (iii) Shear rate is reduced to 0.1 s -1 and (iv) measuring the viscosity of the aqueous pseudoplastic gel composition as a function of time and comparing it to the value of the third viscosity η3. reaches, exhibits or has a fourth viscosity η4 of at least 20%, preferably at least 30%, more preferably at least 50%, even more preferably at least 70% of the value of the third viscosity η3 within 10 seconds, preferably within 5 seconds, more preferably within 2 seconds of the reduction in shear rate in step (iii) of the method comprising: wherein the viscosity is measured in a rheometer with plate-plate geometry and a gap distance of 0.5 mm at a temperature of 25° C.
[0103] In embodiments, the aqueous pseudoplastic gel composition recovers at least 20%, preferably at least 30%, more preferably at least 50%, even more preferably at least 70%, and even more preferably at least 90% by weight of the value of the third viscosity η3 within 10 seconds of the reduction in shear rate in step (iii).
[0104] In an embodiment, the aqueous pseudoplastic gel composition recovers at least 20%, preferably at least 30%, more preferably at least 50% of the value of the third viscosity η3 within 5 seconds of the reduction in shear rate in step (iii).
[0105] In some embodiments, the aqueous pseudoplastic gel composition recovers at least 20%, preferably at least 30%, of the value of the third viscosity η3 within 2 seconds of the reduction in shear rate in step (iii).
[0106] As will become apparent from the accompanying examples, the aqueous pseudoplastic gel composition according to the present invention is able to recover about 100% of the value of the third viscosity η3 after a period of time from the reduction in shear rate in step (iii).
[0107] Method for producing aqueous pseudoplastic gel composition Generally speaking, the components of the aqueous pseudoplastic gel composition can be added in any order. After mixing all the components, the composition is stirred or homogenized, preferably for 5 to 15 minutes, at a temperature of preferably 15 to 30°C. In a preferred embodiment, the thickener is added after mixing the water, spherical glass beads and any further components. The stirring or homogenization is preferably performed at a low shear rate to avoid the inclusion of air bubbles in the aqueous pseudoplastic gel composition.
[0108] As explained above, the thickening effect of the thickening agent may depend on the pH value. Thus, the method for preparing the aqueous pseudoplastic gel composition may include a step of adjusting the pH, for example, adjusting the pH to a value between 6.0 and 11, for example 7.0 to 11, 7.0 to 9.5 or 7.4 to 7.9. The pH can be appropriately adjusted using diluted NaOH or an aminomethylpropanol neutralizer such as AMP Ultra® PC2000.
[0109] Thus, in a second aspect of the present invention, there is provided a method for the preparation of an aqueous pseudoplastic gel composition as defined herein, the method comprising: (i) adding water, spherical glass beads as defined above, a thickening agent as defined above and any one or more further ingredients as defined above to a vessel; (ii) stirring or homogenizing the mixture obtained in step (i) at a temperature preferably between 15 and 30° C., preferably for a period of time between 5 and 15 minutes; and (iii) optionally, before or after step (ii), adjusting the pH, preferably to a value between 6.0 and 11, more preferably to a value between 7.0 and 11. Includes.
[0110] The pH in step (iii) is preferably adjusted to a value between 7.0 and 9.5.
[0111] However, the addition of the different components may also take place at different stages of the process.Accordingly, in a third aspect of the present invention, there is provided a method for the preparation of an aqueous pseudoplastic gel composition as defined herein, the method comprising: (i) adding water, spherical glass beads as defined above, at least a portion of the thickening agent as defined above, and optionally a portion of one or more further ingredients as defined above to a container; (ii) stirring or homogenizing the mixture obtained in step (i) preferably at a temperature of 15-30° C., preferably for a period of 5-15 minutes; (iii) optionally adjusting the pH before or after step (ii), preferably to a value between 6.0 and 11, more preferably to a value between 7.0 and 11; (iv) adding to the composition obtained in step (ii) or (iii) at least a portion of one or more further ingredients as defined above, optionally adding a portion of a thickening agent as defined above, and optionally adding water; (v) stirring or homogenizing the mixture obtained in step (iv) at a temperature preferably between 15 and 30° C., preferably for a period of time between 5 and 15 minutes; and (vi) optionally, before or after step (v), adjusting the pH, preferably to a value between 6.0 and 11, more preferably to a value between 7.0 and 11; Includes.
[0112] The pH in step (vi) is preferably adjusted to a value between 7.0 and 9.5.
[0113] In embodiments, the time between carrying out steps (i)-(iii) on the one hand and carrying out steps (iv)-(vi) on the other hand may be several days or months or even longer.
[0114] The method for preparing an aqueous pseudoplastic gel composition may also involve making an intermediate aqueous pseudoplastic gel composition having the composition and properties defined hereinbefore, followed by adding and mixing another composition to obtain the final aqueous pseudoplastic gel composition, provided that the final aqueous pseudoplastic gel composition still has the composition and properties defined hereinbefore.
[0115] Thus, in a fourth aspect of the present invention, there is provided a method for preparing an aqueous pseudoplastic gel composition as defined above, said method comprising the steps of: (i) adding water, spherical glass beads as defined above, at least a portion of the thickening agent as defined above, and optionally a portion of one or more further ingredients as defined above to a container; (ii) stirring or homogenizing the mixture obtained in step (i) preferably at a temperature of 15-30° C., preferably for a period of 5-15 minutes, to obtain an intermediate aqueous pseudoplastic gel composition having the composition and properties of the aqueous pseudoplastic gel composition as defined herein above; (iii) optionally adjusting the pH before or after step (ii), preferably to a value between 6.0 and 11, more preferably to a value between 7.0 and 11; (iv) adding to the intermediate aqueous pseudoplastic gel composition obtained in step (ii) or (iii) at least a portion of one or more further ingredients as defined above, optionally adding a portion of a thickener as defined above, and optionally adding water; (v) stirring or homogenizing the mixture obtained in step (iv) at a temperature of preferably 15 to 30° C. for preferably 5 to 15 minutes to obtain an aqueous pseudoplastic gel composition; and (vi) optionally, before or after step (v), adjusting the pH, preferably to a value between 6.0 and 11, more preferably to a value between 7.0 and 11; Includes.
[0116] The pH in step (vi) is preferably adjusted to a value between 7.0 and 9.5.
[0117] In embodiments, the time between carrying out steps (i)-(iii) on the one hand and carrying out steps (iv)-(vi) on the other hand may be several days or months or even longer.
[0118] How to coat the substrate In a fifth aspect, the present invention provides a method of coating a substrate with a retroreflective layer, comprising: (a) providing a substrate; (b) optionally applying a primer layer to the substrate of step (a); (c) spraying an aqueous pseudoplastic gel composition as defined above onto the substrate of step (a) or onto the primed substrate of step (b) to provide a substrate coated with a retroreflective layer; (d) optionally drying the substrate coated with the retroreflective layer obtained in step (c); and (e) coating the retroreflective layer-coated substrate obtained in step (c) or the dried retroreflective layer-coated substrate obtained in step (d) with one or more additional transparent coating layers, followed by drying or curing. The present invention relates to a method comprising the steps of:
[0119] Step (c) of spraying the aqueous pseudoplastic gel composition can involve spraying a single layer in one step, or spraying multiple layers on top of each other in subsequent spraying steps.
[0120] In one embodiment, step (b) is performed. The basecoat layer applied in step (b) can be a pigmented basecoat layer, for example, comprising mica flake pigment or metal flakes or powders.
[0121] The shape of the substrate to be coated is not limited in any way, as long as it can be coated by spraying, i.e., droplets of the aqueous pseudoplastic gel composition can reach the surface of the substrate. In an embodiment, the substrate is flat. In another embodiment, the substrate is curved. In a further embodiment, the substrate includes flat and curved portions.
[0122] The inventors have established that the aqueous pseudoplastic gel composition can be applied to various substrates, for example, using industrial high-speed spraying, to produce a retroreflective coating layer with excellent print or coating quality, for example, homogeneity and retroreflectivity at wide angles. When the retroreflective coating layer is provided with one or more additional transparent coating layers (i.e., when step (e) of the method for coating a substrate defined above is performed), a retroreflective layer with high smoothness and good washability is obtained. Unexpectedly, these results can also be obtained when the aqueous pseudoplastic gel composition is applied to the surface of a substrate that is vertically arranged.
[0123] In a preferred embodiment, the substrate is selected from textiles, leather, metal, concrete, rubber, plastic, carbon fiber, and combinations thereof.Textiles as used herein include woven or knitted textile fabrics such as cotton, polyester, nylon, silk, wool, viscose, and acrylic.
[0124] Regardless of the type of material from which the substrate is made, the substrate may be selected from the group consisting of clothing, traffic signs, vehicle chassis, bicycle frames, roads, pavements, and guardrails.
[0125] The substrate with the retroreflective coating according to the present invention may be provided with one or more additional transparent coating layers in step (e). These one or more additional transparent coating layers may serve to protect the retroreflective layer from scuffing and / or moisture. In addition, they may be used to provide a specific matte or gloss / shiny appearance to the substrate coated with the retroreflective layer. The one or more additional transparent coating layers may be pigmented. The one or more additional transparent coating layers applied in optional step (e) may include a liquid coating layer, a powder coating layer or a combination thereof, which are subsequently cured or dried.
[0126] The spraying in step (c) is preferably carried out using a spray gun. In one embodiment, the spraying is carried out with a propellant. In a preferred embodiment, the spraying is carried out without the use of a propellant.
[0127] The drying in optional step (d) and drying or curing in step (f) can be carried out under ambient conditions, or can be carried out at elevated temperatures and / or reduced pressure.
[0128] In a preferred embodiment, the aqueous pseudoplastic gel composition is prepared in step (c) by dissolving the aqueous pseudoplastic gel composition in a substrate. 2 The amount is preferably 60 to 250 g per m 2 and even more preferably in an amount of 80-225 g per m 2 These amounts can be sprayed as a single layer in one step or as multiple layers on top of each other in subsequent spraying steps.
[0129] In a sixth aspect, the present invention relates to a substrate coated with a retroreflective layer obtained by the method defined above. The substrate coated with the retroreflective layer can have a matt or glossy appearance.
[0130] In a preferred embodiment, the substrate coated with a retroreflective layer, preferably coated with one or more further transparent coating layers (i.e. step (e) of the method for coating a substrate defined above is performed), exhibits retroreflection of the retroreflective layer at any angle from 0 to 80°, e.g. 0 to 78°, 0 to 75°, 0 to 70°, 0 to 65°, 0 to 60°, 0 to 55°, 0 to 50°, 0 to 45°, and 0 to 40° from the normal of the coated substrate. This retroreflection of the retroreflective layer is determined by directing the beam of a torch at the retroreflective layer, where the line of sight of the eye is substantially coincident with the beam of the torch, and visually determining whether retroreflection is observed. The experiment starts at an angle of 0 to the normal of the coated substrate, and then gradually increases the angle until retroreflection is no longer noticeable.
[0131] The invention has thus been described with reference to the specific embodiments outlined above, it being recognized that these embodiments are susceptible to various modifications and alternatives that will be apparent to those skilled in the art.
[0132] Moreover, for a proper understanding of this specification and its claims, it should be understood that the verb "to comprise" and its conjugations are used in their open-ended sense to mean that items not specifically mentioned are not excluded. Moreover, reference to an element by the indefinite article "a" or "an" does not exclude the possibility that there is more than one of that element, unless the context clearly requires that there be only one of that element. Thus, the indefinite article "a" or "an" typically means "at least one."
[0133] [Example] <Example 1> Five aqueous pseudoplastic gel compositions according to the invention were prepared at ambient temperature (about 20° C.) by adding the ingredients to a container in the following order: (1) demineralized water, (2) spherical glass beads, (3) further ingredients, (4) thickener. If necessary, the pH was adjusted by adding AMP Ultra PC2000 (further ingredient). The resulting mixture was mixed again at ambient temperature for about 10 minutes. The amounts of the various ingredients are shown in Table 1. The following ingredients were used:
[0134] Spherical Glass Beads SFX 2.2 (obtained from Jianxi Sunflex Light Retroreflective Material Co., Ltd.) has a refractive index of about 2.2 measured at a wavelength λ = 589 nm, a median particle size D50 of 40.37 μm, a D10 diameter of 37.32 μm, and a D90 diameter of 44.11 μm measured by laser diffraction, and a specific gravity of about 4.5 g / cm 3 These spherical glass beads contain TiO2, BaO, ZnO and CaO.
[0135] Further ingredients Kuncai Gold Finch 10-60μm, obtained from Kuncai. Mica Syntran KL219 CG, available from Interpolymer; a film-forming polymer Optiphen, available from Ashland Specialty Ingredients; a preservative Syntran 5778, available from Interpolymer; a film-forming polymer Citrofol, available from Jungbunzlauer; plasticizer Worlee Colour Yellow, available from Worlee; pigment AMP Ultra PC 2000, available from Angus Chemical Company; neutralizer Glitsa® Normaal Gebruik Parketlak Kleurloos, available from Akzo Nobel; water-based parquet varnish Ceta Bever® Schuur&Tuinhuis Beits, Blank Transparent Zijdeglans, Akzo Nobel; Water-based dyes Sikkens Autowave™ MM2.0, available from Akzo Nobel, water-based basecoat for automobiles Acticide MBL, available from Thor; preservative
[0136] Thickener Carbopol® Aqua SF-1, available from Lubrizol, a crosslinked acrylate copolymer thickener Aquatix 8421, available from BYK; thickener, non-ionic aqueous emulsion of modified ethylene vinyl acetate copolymer wax Rheobyk-420, available from BYK, modified urea thickener Rheovis® AS 1152, available from BASF, ASE thickener ACULYN™ Excel, available from DOW Chemical, a HASE thickener
[0137] [Table 1]
[0138] <Example 2> The stability of the five aqueous pseudoplastic gel compositions shown in Table 1 was evaluated by visual and tactile inspection to see if the samples exhibited settling, syneresis or separation (phase or otherwise). A sample is considered stable if no settling, syneresis or separation is observable upon visual and tactile inspection. The pH of the five compositions immediately after synthesis and their subsequent stability are listed in Table 2.
[0139] [Table 2]
[0140] <Example 3> The rheological behavior of the five compositions shown in Table 1 was measured at a temperature of 25.0° C. using a Malvern Kinexus Rheometer with a plate-plate geometry (PL40 plate) and a gap distance of 0.5 mm.
[0141] The viscosity versus shear rate profiles of five aqueous pseudoplastic gel compositions according to the present invention were measured at about 0.0001 s -1 ~1000s -1 The viscosity versus shear rate profiles are shown in Figure 1. As can be inferred from Figure 1, all aqueous pseudoplastic gel compositions exhibit shear thinning behavior. The shape of the viscosity versus shear rate profiles in the limit of zero shear rate suggests that the compositions do not have a yield point. All five aqueous pseudoplastic gel compositions were flowable.
[0142] Thixotropy tests were then carried out by applying three shear rate regimes and measuring the viscosity as a function of time. In the first regime, 0.1 s -1 A shear rate of 100 s was applied for approximately 30–60 s and the viscosity was measured with a sampling interval of 2 s. In the second regime, the shear rate was increased to 100 s -1 In the third regime, the shear rate was increased to 0.1 s and the viscosity was measured for 30 s with a sampling interval of 2 s. -1 and the viscosity was measured for 600 seconds with a sampling interval of 1 second. Figure 2 shows the thixotropic behavior of the five aqueous pseudoplastic gel compositions of Figure 1. As can be inferred from Figure 2, all aqueous pseudoplastic gel compositions recover at least 50% of the viscosity measured in the first regime within a few seconds of the start of the third regime. Furthermore, the aqueous pseudoplastic gel compositions are able to recover about 100% of the viscosity value of the first regime.
[0143] Furthermore, frequency sweep tests were performed to evaluate the viscoelastic behavior of the four aqueous pseudoplastic gel compositions. The loss modulus G”, storage modulus G’ and tan(δ) were measured for 10 samples / decade at appropriate shear strains within the linear viscoelastic range, with oscillation frequencies varying between 10 Hz and 0.1 Hz. The results are shown in Figure 3. The tan(δ) values are all less than 1 over the range of oscillation frequencies, indicating gel-like behavior in the sense that the elastic behavior dominates the viscous behavior.
[0144] <Example 4> The five aqueous pseudoplastic gel compositions described in Example 1 were sprayed onto a vertically oriented flat metal test plate (10 x 15 cm) at a pressure of 2.2 bar using a spray gun (DeViLBISS HVLP, DV1-C1 Plus) with a 1.3 mm nozzle, with a thickness of 1 m. 2 The sprayed layer was applied in an amount of about 130 g per layer. The sprayed layer was air-dried at ambient temperature. After drying, a visually attractive retroreflective layer was obtained with very good quality in terms of smoothness and homogeneity. Thus, industrial spraying on vertically arranged substrates is possible without, for example, resulting in sagging or inhomogeneous layers.
[0145] Metal test plates coated with the five aqueous pseudoplastic gel compositions were further coated with a transparent reactive Sikkens® Aerodry two-component lacquer (Akzo Nobel) and subsequently cured. The retroreflection of the resulting retroreflective layer was determined by directing the beam of a torch at the retroreflective layer, substantially aligning the line of sight of the eye with the beam of the torch, and visually determining whether retroreflection was observed. The experiment started at an angle of 0 to the normal of the coated substrate, and then the angle was gradually increased until retroreflection was no longer noticeable. The substrates coated with the retroreflective layer showed clear retroreflection of the retroreflective layer at all angles from 0 to 80° from the normal of the coated substrate.
[0146] <Example 5> The viscosities of the compositions in Table 1 of Example 1 were measured with a Brookfield viscometer using a #5 spindle rotating at 10 rpm, and the results are shown in Table 3.
[0147] [Table 3]
[0148] The Brookfield viscosities obtained using a #5 spindle rotating at 10 rpm are thus 1.4-6 Pa·s, which is well below the lower values required for screen printing (inks) as disclosed in WO 00 / 42113 A1.
Claims
1. 0.01s -1 A first viscosity η of 5 to 200 Pa·s at a shear rate of 1 , and 100s -1 a second viscosity η 10 to 1000 times lower than the first viscosity at a shear rate of 2 1. An aqueous pseudoplastic gel composition comprising: 15-60% by weight of water; - 20-60% by weight of spherical glass beads having a median particle size D50 of 5-150 μm as measured by laser diffraction and a refractive index of 1.8-2.8 as measured at a wavelength λ of 589 nm, optionally at least a portion of said spherical glass beads being hemispherically coated with a light reflective coating; 0.15 to 1.5% by weight of a thickening agent; and 0-50% by weight of one or more further ingredients and the viscosity is measured at a temperature of 25° C. with a rheometer having a plate-plate geometry and a gap distance of 0.5 mm.
2. 0.1s -1 The third viscosity η 3 2. The aqueous pseudoplastic gel composition of claim 1, comprising: The aqueous pseudoplastic gel composition is subjected to the successive steps: (i) The aqueous pseudoplastic gel composition is mixed with water for 0.1 s. -1 and subjecting the mixture to a shear rate of η for at least 30 seconds. 3 measuring the (ii) The aqueous pseudoplastic gel composition is mixed with water for 100 s. -1 for 30 seconds; (iii) Shear rate is 0.1 s -1 to; and (iv) measuring the viscosity of the aqueous pseudoplastic gel composition as a function of time. Within 10 seconds of the reduction in shear rate in step (iii) of the method comprising: 3 and the viscosity is measured at a temperature of 25° C. with a rheometer having a plate-plate geometry and a gap distance of 0.5 mm.
3. 3. The aqueous pseudoplastic gel composition according to claim 1, which has a tan(δ) value of less than 1, measured with a rheometer having a plate-plate geometry and a gap distance of 0.5 mm at a temperature of 25° C. and a vibration frequency of 10 to 0.1 Hz.
4. 4. The aqueous pseudoplastic gel composition according to claim 1, wherein the spherical glass beads have a refractive index of 2.0 to 2.8, measured at a wavelength λ of 589 nm.
5. 5. The aqueous pseudoplastic gel composition according to claim 1, comprising 0.20 to 1.4 wt. % of said thickener, based on the total weight of said aqueous pseudoplastic gel composition.
6. 6. The aqueous pseudoplastic gel composition of any one of claims 1 to 5, wherein the thickening agent is selected from the group consisting of ASE polymers, HASE polymers, HEUR polymers, liquid acrylic crosslinks or copolymer dispersions, acrylate crosspolymers, crosslinked polyacrylic acid polymers, crosslinked polyacrylic acid copolymers, non-ionic aqueous emulsions of modified ethylene vinyl acetate copolymer waxes, modified ureas or urea modified polyamides, and combinations thereof.
7. 7. The aqueous pseudoplastic gel composition according to any one of claims 1 to 6, which is stable for at least one day, and is considered stable when no settling, syneresis or separation is observed upon visual and tactile inspection.
8. The aqueous pseudoplastic gel composition of any one of claims 1 to 7 which is an ink, paint or coating formulation.
9. A method for preparing the aqueous pseudoplastic gel composition according to any one of claims 1 to 8, (i) adding water, spherical glass beads, a thickening agent and optionally one or more additional ingredients to a container; (ii) stirring or homogenizing the mixture obtained in step (i); and (iii) optionally adjusting the pH before or after step (ii). A preparation method comprising:
10. A method for preparing the aqueous pseudoplastic gel composition according to any one of claims 1 to 8, (i) adding water, spherical glass beads, at least a portion of the thickening agent and optionally a portion of one or more further ingredients to a container; (ii) stirring or homogenizing the mixture obtained in step (i); (iii) optionally adjusting the pH before or after step (ii); (iv) adding at least a portion of one or more further ingredients to the composition obtained in step (ii) or (iii), optionally adding a portion of the thickener, and optionally adding water; (v) stirring or homogenizing the mixture obtained in step (iv); and (vi) optionally adjusting the pH before or after step (v); A preparation method comprising:
11. A method of coating a substrate with a retroreflective layer comprising: (a) providing a substrate; (b) optionally applying a primer layer to the substrate of step (a); (c) spraying the aqueous pseudoplastic gel composition of any one of claims 1 to 8 onto the substrate of step (a) or onto the primed substrate of step (b) to provide a substrate coated with a retroreflective layer; (d) optionally drying the substrate coated with the retroreflective layer obtained in step (c); and (e) coating the retroreflective layer-coated substrate obtained in step (c) or the dried retroreflective layer-coated substrate obtained in step (d) with one or more additional transparent coating layers, followed by drying or curing. The method includes:
12. 12. The method of claim 11, wherein the aqueous pseudoplastic gel composition is applied to the substrate in step (c) using a spray gun.
Citation Information
Patent Citations
retroreflective ink
JP2002534576A
Retroreflecting watercolor
JP2003213213A
Fine sphere for retroreflection, retroreflective coating and retroreflective printed material
JP2005105222A
Coating method and retroreflective coating material used for the same
JP2011206655A
Retroreflective coating, coated film and substrate
JP2017101194A